Nootropics as Cognitive Enhancers: Types, Dosage and Side Effects of Smart Drugs - Malík, Matěj; Tlustoš, Pavel (Nutrients, 2022)
Nootropics, also known as "smart drugs" are a diverse group of medicinal substances whose action improves human thinking, learning, and memory, especially in cases where these functions are impaired. This review provides an up-to-date overview of the potential effectiveness and importance of nootropics. Based on their nature and their effects, this heterogeneous group of drugs has been divided into four subgroups: classical nootropic compounds, substances increasing brain metabolism, cholinergic, and plants and their extracts with nootropic effects. Each subgroup of nootropics contains several main representatives, and for each one, its uses, indications, experimental treatments, dosage, and possible side effects and contraindications are discussed. For the nootropic plant extracts, there is also a brief description of each plant representative, its occurrence, history, and chemical composition of the medicinal part. Lastly, specific recommendations regarding the use of nootropics by both ill and healthy individuals are summarized.
Keywords: ayurvedic; Paullinia cupana; Drug-Related Side Effects and Adverse Reactions; Panax ginseng; učení; piracetam; nootropní látky; Humans; Nootropic Agents; learning; nootropics; lidé; nežádoucí účinky léčiv; memory; smart drugs; Learning; brain injury; antioxidant activity